The battle of Bretton Woods : John Maynard Keynes, Harry Dexter White, and the making of a new world order - Steil, Benn (Princeton University Press, 2013)
When turmoil strikes world monetary and financial markets, leaders invariably call for 'a new Bretton Woods' to prevent catastrophic economic disorder and defuse political conflict. The name of the remote New Hampshire town where representatives of forty-four nations gathered in July 1944, in the midst of the century's second great war, has become shorthand for enlightened globalization. The actual story surrounding the historic Bretton Woods accords, however, is full of startling drama, intrigue, and rivalry, which are vividly brought to life in Benn Steil's epic account.